Respuesta :
Answer:
64
Step-by-step explanation:
Evaluate x^4 + 3 x^3 - 6 x^2 - 12 x - 8 where x = 3:
x^4 + 3 x^3 - 6 x^2 - 12 x - 8 = 3^4 + 3×3^3 - 6×3^2 - 12×3 - 8
3^3 = 3×3^2:
3^4 + 3×3×3^2 - 6×3^2 - 12×3 - 8
3^2 = 9:
3^4 + 3×3×9 - 6×3^2 - 12×3 - 8
3×9 = 27:
3^4 + 3×27 - 6×3^2 - 12×3 - 8
3^2 = 9:
3^4 + 3×27 - 69 - 12×3 - 8
3^4 = (3^2)^2:
(3^2)^2 + 3×27 - 6×9 - 12×3 - 8
3^2 = 9:
9^2 + 3×27 - 6×9 - 12×3 - 8
9^2 = 81:
81 + 3×27 - 6×9 - 12×3 - 8
3×27 = 81:
81 + 81 - 6×9 - 12×3 - 8
-6×9 = -54:
81 + 81 + -54 - 12×3 - 8
-12×3 = -36:
81 + 81 - 54 + -36 - 8
81 + 81 - 54 - 36 - 8 = (81 + 81) - (54 + 36 + 8):
(81 + 81) - (54 + 36 + 8)
| 8 | 1
+ | 8 | 1
1 | 6 | 2:
162 - (54 + 36 + 8)
| 1 |
| 5 | 4
| 3 | 6
+ | | 8
| 9 | 8:
162 - 98
| | 15 |
| 0 | 5 | 12
| 1 | 6 | 2
- | | 9 | 8
| 0 | 6 | 4:
Answer: 64
Answer: 64
Step-by-step explanation:
f(x) = x⁴ + 3x³ - 6x² -12x -8
when x= 3
f(3) = (3)⁴ + 3(3)³ - 6(3)² -12(3) -8
=81 + 3(27) - 6(9)- 12(3) - 8
= 81 + 81 - 54 - 36 - 8
= 64
Therefore, when x= 3 the function becomes; f(3)=64